2022
DOI: 10.25273/jipm.v11i1.13161
|View full text |Cite
|
Sign up to set email alerts
|

The Effectivenes Of The Missouri Mathematics Project Model on Creative Thinking Ability and Self-Efficacy

Abstract: <p>Kemampuan untuk berpikir kreatif matematis dapat dikatakan sebagai kapabilitas kognitif untuk mengajukan dan mempertimbangkan informasi sehingga dapat memberikan perbedaan dari gagasan serta menjadikan pengetahuan yang baru dalam menunjang keberhasilan dalam pembelajaran. Penelitian ini disusun dengan maksud agar dapat memahami bagaimana model pembelajaran Missouri Mathematics Project (MMP) dapat bekerja efektif pada kapabilitas berpikir kreatif matematis dan efikasi yang ada pada diri siswa SMA. Penu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Similarly, it aimed to describe the characteristics of students' mathematical creative thinking skills based on selfconfidence, indicating a link between self-confidence and creative thinking in mathematics . Furthermore, the research demonstrated a positive influence between self-efficacy and creative thinking ability, suggesting that higher leads to more persistent efforts when faced with difficulties or problems (Faradillah & Purwitasari, 2022).…”
Section: Data On Creative Thinking Ability Test Resultsmentioning
confidence: 83%
“…Similarly, it aimed to describe the characteristics of students' mathematical creative thinking skills based on selfconfidence, indicating a link between self-confidence and creative thinking in mathematics . Furthermore, the research demonstrated a positive influence between self-efficacy and creative thinking ability, suggesting that higher leads to more persistent efforts when faced with difficulties or problems (Faradillah & Purwitasari, 2022).…”
Section: Data On Creative Thinking Ability Test Resultsmentioning
confidence: 83%